The Relationship of Individual Characteristics With the Use of PPE at Workers of Public Fuel Filling Station (Spbu) in South Aceh Regency - Nilawati (Science Midwifery, 2022)
he job that gets much exposure to gasoline is selling gasoline, exposed to gasoline fumes quite often. Workers are significantly at risk of DNA damage due to the genotoxic nature of these substances. Currently, there are still many gas station workers who do not use PPE when working. Workers do not seem to pay attention and maintain personal hygiene while working. After holding the gas station and holding the money directly, eat food. Protective equipment in the workplace is often neglected by workers or employees, even by workplace management. Therefore, this study aims to analyze the characteristics of individuals using PPE at Public Fuel Filling Station (SPBU) workers. Method: This type of research is cross-sectional. The population is 46 people; using Saturated Sampling, that is the whole population. Results: the results of the study found that there was a relationship between Age, Education, Marital Status, and Period of Service with the Use of Personal Protective Equipment (PPE) at Public Fuel Filling Station (Spbu) Workers in South Aceh Regency as evidenced by a value > 0.0 00. The group that completed PPE was more dominant than the female sex group as many as ten people (62.5%), aged 30 years ten people (71.4%), secondary education 12 people (63.2%), marital status 11 people (68.8%), 11 people (64.7%), the p-value for each indicator is less than 0.05, so there is a significant relationship between each characteristic: gender, age, education, marital status, and years of service with the use of Personal Protective Equipment (PPE). Female gender, age group more than or equal to 30 years, married status, secondary education, and working period of more or equal to 2 years are more aware of completing PPE. It is recommended that male workers under 30 years, unmarried, with primary education, and working period of under two years must use complete PPE when working. Companies and the government pay attention to the safety and health of workers.